Assessment of physical, mechanical, and biological properties of bamboo plastic composite made with polylactic acid - Dehghan, Moein; Faezipour, Mehdi; Azizi, Majid; Zarea Hosseinabadi, Hamid; Bari, Ehsan; D. Nicholas, Darrel (Maderas. Ciencia y Tecnología, 2019)
The effects of different mixing, bamboo mesh size and heat treatment on the physical and mechanical properties and biodegradability of a polylactic acid (PLA) composite were determined. The results indicated that this composite exhibited high strength in all mechanical properties examined, except hardness using the pure polymer (PLA). The mesh size of the bamboo flour and heat treatment had considerable effects on all tests expect the decay resistance. The water absorbance and thickness swelling of the PLA composite was reduced to nearly zero after 3000 hours immersion in water. Moreover, the fungal decay test results demonstrated that PLA was highly resistant to both Basidiomycetes and Ascomycetes fungi. The brown rot fungi, however, produced an extensive mass loss in the composite composed of different levels of bamboo flour.